Development and validation of Mayaro virus with luciferase reporter genes as a tool for antiviral assays - Marinho, Mikaela dos Santos; Zhang, Ya-Nan; Cassani, Natasha Marques; Santos, Igor Andrade; Costa Oliveira, Ana Laura; dos Santos Pereira, Anna Karla; Corbi, Pedro Paulo; Zhang, Bo; Jardim, Ana Carolina Gomes [UNESP] (Elsevier, 2024)
Arboviruses are etiological agents in an extensive group of emerging diseases with great clinical relevance in Brazil, due to the wide distribution of their vectors and the favorable environmental conditions. Among them, the Mayaro virus (MAYV) has drawn attention since its emergence as the etiologic agent of Mayaro fever, a highly debilitating disease. To study viral replication and identify new drug candidates, traditional antiviral assays based on viral antigens and/or plaque assays have been demonstrating low throughput, making it difficult to carry out larger-scale assays. Therefore, we developed and characterized two DNA-launched infectious clones reporter viruses based on the MAYV strain BeAr 20290 containing the reporter genes of firefly luciferase (FLuc) and nanoluciferase (NLuc), designated as MAYV-firefly and MAYV-nanoluc, respectively. The viruses replicated efficiently with similar properties to the parental wild-type MAYV, and luminescence expression levels reflected viral replication. Reporter genes were also preserved during passage in cell culture, remaining stably expressed for one round of passage for MAYV-firefly and three rounds for MAYV-nanoluc. Employing the infectious clone, we described the effect of Rimantadine, an FDA-approved Alzheimer's drug, as a repurposing agent for MAYV but with a broad-spectrum activity against Zika virus infection. Additionally, we validated MAYV-nanoluc as a tool for antiviral drug screening using the compound EIDD-2749 (4′-Fluorouridine), which acts as an inhibitor of alphavirus RNA-dependent RNA polymerase.
Keywords: Antiviral; Mayaro virus; Reporter virus; Rimantadine hydrochloride; Zika virus